EVALUASI SIKLUS PENDAPATAN RSUD Dr. RADEN SOEDJATI SOEMODIARDJO PURWODADI KABUPATEN GROBOGAN - Ismining Rahayu, Djoko Kristianto & Muhammad Rofiq Sunarko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
This research aims to know the affectiveness of hospital revenuecycle. This reseach was qualitive research with data collection techniques in the from of observation, interview, questionnaire and documentation. Engineering analysis result using comparative analysis techniques or comparisons. Movie based on analysis result showed that the flowchart system or procedures used have not been affective. The result of the analysis based on the answers of respondents towards internal control questionnaires compiled based on COSO, obtain an overall effective results with good criteria occupies. Keywords: revenue cycle, internal control, hospital